Regulating False Discloure - Maarten Janssen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Firms can communicate private information about product quality through a combination of pricing and disclosure where disclosure may be deliberately false. We examine the effect of regulation that penalizes false disclosure by firms in a competitive setting. The cost of false disclosure influences the mix of direct, costly information provision and price signaling in the market, and thereby market outcomes. Regulation reduces prices and the consumption distortion associated with price signaling.
Keywords: L13; L15; D82; D43; 330